The role of Hsp0, CD-8 and IFN-γ in immunopathobiogenesis of periapical granuloma in dental caries - Risya Cilmiaty; Mandojo Rukmo (Dental Journal (Majalah Kedokteran Gigi), 2014)
Background: The incidence of dental caries with periapical granulomas in Indonesia is quite high. However, the mechanism of the formation of periapical granulomas in dental caries caused by bacterial infection in immunopathobiogenesis cannot be explained completely. Thus, this explanation is necessary in order to be used as a basis for diagnostic, preventive and therapeutic measures. Purpose: This research was aimed to determine the role of Hsp60, CD-8 and IFN-γ in immunopatobiogenesis of periapical granuloma in dental caries. Methods: This research was an analytic observational study with cross sectional approach. Samples of this research were 36 teeth of patients with dental caries, consisting of 18 caries teeth with periapical granulomas and 18 caries teeth without periapical granulomas. The variables observed in this research were Hsp60, CD-8 and IFN-γ. Measurements were conducted by using immunohistochemical methods on periapical tissue. Results: The mean of Hsp60, CD-8 and IFN-γ in granuloma group was significantly higher than those in non granuloma group (p<0.05). The positive role of IFN-γ on the incidence of granulomas appeared to be more prominent. Conclusion: The study suggested that in immunopathobiogenesis of periapical granuloma in dental caries, Hsp60, CD-8 and IFN-γ played important roles, but the role of IFN-γ was found to be more prominent.Latar belakang: Angka kejadian gigi karies dengan granuloma periapikal di Indonesia cukup tinggi, Namun mekanisme terbentuknya granuloma periapikal pada gigi karies yang disebabkan oleh infeksi bakteri secara imunopatobiogenesis belum dapat dijelaskan secara tuntas. Adanya penjelasan ini diperlukan agar dapat digunakan sebagai dasar pengembangan diagnosis, langkah preventif dan terapinya. Tujuan: Penelitian ini bertujuan untuk mengetahui peran Hsp60, CD-8 dan IFN-γ dalam immunopatobiogenesis dari granuloma periapikal karies gigi. Metode: Penelitian ini merupakan penelitian observasional analitik dengan pendekatan cross sectional. Sampel dari penelitian ini adalah 36 gigi pasien dengan karies, yang terdiri dari 18 karies gigi dengan granuloma periapikal dan 18 karies gigi tanpa granuloma periapikal. Variabel yang diamati adalah Hsp60, CD-8 dan IFN-γ. Pengukuran dilakukan dengan menggunakan metode imunohistokimia pada jaringan periapikal. Hasil: Rerata Hsp60, CD-8 dan IFN-γ pada kelompok granuloma secara signifikan lebih tinggi dibanding kelompok non granuloma (p <0,05). Peran positif dari IFN-γ terhadap kejadian granuloma tampaknya lebih menonjol. Simpulan: Studi ini menunjukkan bahwa dalam imunopatobiogenesis dari granuloma periapikal karies gigi, Hsp60, CD-8 dan IFN-γ memainkan peran penting, tetapi peran IFN-γ ditemukan lebih menonjol.